Disability and COVID-19: Representation and Resilience in Graphic Novels - Karmakar, Debasish (Integrated Journal for Research in Arts and Humanities, 2023)
The COVID-19 pandemic has presented unique challenges for individuals with disabilities, and graphic novels have emerged as a powerful medium for representing and exploring these experiences. Historically, disabled individuals have been underrepresented and depicted in stereotypical ways, but graphic novels have challenged these narratives by offering authentic portrayals that humanize disabled characters. In the context of COVID-19, graphic novels provide a platform to address the intersectionality of disability and the pandemic, highlighting issues such as limited healthcare access, social isolation, and the impact of public health policies. These novels also explore themes of resilience, adaptation, and the triumph of the human spirit, showcasing disabled characters overcoming obstacles and utilizing their strengths and capabilities. Moreover, graphic novels have the potential to raise awareness, challenge stereotypes, and foster empathy and understanding among readers. By amplifying the voices of disabled creators, these novels contribute to a more inclusive literary landscape, challenging traditional narratives that have marginalized disabled individuals. Overall, graphic novels offer a unique opportunity to represent the experiences of disabled individuals during the COVID-19 pandemic, promoting social change and advocating for a more compassionate and equitable society.